Potential Value of Cerebrospinal Fluid Progranulin in the Identification of Postoperative Delirium in Geriatrics Patients Undergoing Knee Replacement: The Perioperative Neurocognitive Disorder and Biomarker LifestylE Study - Wang, Bin; Sun, Xiujie; Wang, Jiahan; Deng, Xiyuan; Lin, Yanan; Liu, Fanghao; Dong, Rui; Lin, Xu; Bi, Yanlin (Frontiers in Aging Neuroscience, 2022)
Objective:The aim of this study was to investigate whether cerebrospinal fluid (CSF)progranulin (PGRN) levels are associated with postoperative delirium(POD) undering knee replacement in geriatric patients. Methods: A total of 600 Han Chinese patients over the age of 65~ 90 who underwent unilateral total knee arthroplasty were included in the Perioperative Neurocognitive Disorder And Biomarker LifestylE study (PNDABLE) from June 2020 to November 2020. All participants were assessed using Confusion Assessment Method (CAM) and the Memorial Delirium Assessment Scale (MDAS) on postoperative 1–7 days (or before discharge) by an anesthesiologist. CSF PGRN and CSF biomarkers of POD were measured by ELISA. We analyze the risk and protective factors of POD by the multivariate logistic regression analysis and also analyze the associations between CSF PGRN and CSF biomarkers of POD by multiple linear regression. We analyze whether the influences of CSF PGRN on POD were mediated by POD core pathology by linear regression models. Results: POD incidence was 9.7% (53/545). There were significant differences in preoperative CSF PGRN between POD and NPOD patients. The multivariate logistic regression analysis showed that CSF Aβ1–40,CSF T-tau and CSF P-tau were risk factors for POD, while CSF PGRN and CSF Aβ1–42 were protective factors for POD. CSF PGRN was positive associated with CSF Aβ1–42 and was negative associated with Aβ1–40 ,T-tau and P-tau in POD patients. We found the influences of CSF PGRN on POD were mediated by POD core pathology. The effect was considered partial mediation with the proportion of mediation varying from44.92% to 62.07%. Conclusion: CSF PGRN is one of the preoperative protective factors for POD. Overall, amyloid pathology and tau protein might partially mediate the influences of PGRN on POD.